Hygienic Aspects of Studying Working Conditions in Furniture Production (Texas Journal of Medical Science, 2023)
the working conditions of furniture production workers according to the hygienic classification of working conditions in terms of harmfulness and danger of factors of the working environment, the severity and intensity of the labor process can be characterized as "harmful" of the third class of the second degree of working conditions (3.2). Our research allowed us to substantiate the priority areas of the system of preventive measures aimed at reducing the negative impact of labor process factors on the health of workers.